Internationalization strategy choice: Case study of Huawei and Apple - PAN, HONGZHUO (2016)
This dissertation tries to explore internationalization strategy choices for MNEs from developed and emerging markets through the investigations of their internationalization motivations, the process of foreign market selection and entry modes choices. By the applications of Dunning’s OLI theory, Institution-based view and the Uppsala model, the internationalization strategy choices that applied by MNEs from developed and emerging market are well examined. Finally, this dissertation makes a detailed comparison between these two kinds of MNEs and concludes their difference and similarities in terms of their internationalization strategy. In this dissertation, the method of case study is used as the research method to investigate the internationalization strategy choices for MNEs from developed and emerging markets. Huawei and Apple are chosen as the representatives for these two kinds of MNEs. Through the comparison between Huawei and Apple, the different internationalization strategy choices for MNEs from developed and emerging markets are concluded and well analysed. Furthermore, some suggestions are provided for the future development of MNEs and also some limitations of this dissertation are presented.